Galactic Center Observations with CTAO LST-1 - Abe Shotaro; Abhishek; Doro Michele; Inada Tomohiro; Strzys Marcel; Teshima Masahiro; Vovk Ievgen (EPJ Web of Conferences)
Very-high-energy gamma-ray observations of the central part of the Milky Way Galaxy allow for morphological study of cosmic-ray propagation around the supermassive black hole Sgr A*. An interpretation of the diffuse gamma-ray component, which spans a few hundred parsecs in longitude, is the PeVatron scenario: the spectral energy distribution follows a power law up to a few tens of TeV, with a spatial distribution that is aligned with the central molecular zone and accelerated cosmic rays that propagate in the vicinity of Sgr A*. Nevertheless, differences in the findings of earlier studies persist among current-generation telescopes, each offering different interpretations based on different analytical approaches. The MAGIC telescopes for example presented a hint of a presence of a spectral turnover at around 20 TeV, possibly in tension with the PeVatron scenario. We analyzed Galactic Center data taken by the Large-Sized Telescope prototype (LST-1) for the Cherenkov Telescope Array Observatory (CTAO), the next-generation project of a ground-based gammaray observatory currently under commissioning. Despite the limited sensitivity due to the current monoscopic observation, the relatively wide field of view and the large-zenith-angle observation technique allow LST-1 to study the diffuse emission in the TeV range. In this contribution, we will report the current status of studies of the Galactic Center diffuse emission by including our results from LST-1 observations.